Taxes depress corporate borrowing: Evidence from private firms - Ivan T. Ivanov; Luke Pettit; Toni Marion Whited (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2021)
We re-examine the relation between taxes and corporate leverage, using variation in state corporate income tax rates. In contrast with prior research, we document that corporate leverage increases following tax cuts for both privately held and publicly listed firms. We use an estimated dynamic equilibrium model to show that tax cuts result in lower default spreads and more distant default thresholds. These effects outweigh the loss of benefits from the interest tax deduction and lead to higher leverage, especially for privately held firms. Overall, debt tax shields appear to be a secondary capital structure consideration.
Keywords: 330